A Study of Using QUEFTS Model for Establishing Site Specific Fertilizer Recommendation in Maize on The Basis of Farmer Fields - Wijayanto, Yagus; Prastyanto, Edy (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2011)
Nutrient Use Efficiency (NUE) of Maize is considered low. There are two important factors responsible for this condition: (a) uniform fertilizer recommendation, (b) lack of consideration on soil variability, Indigenous Nutrient Supply and plant nutrient needs. A method for studying low NUE and the capability of studying these two factors are urgently required. This study used Quantitative Evaluation of Fertility on Tropical Soils (QUEFTS) model. The main aim of this study was to employ and evaluate QUEFTS model for establishing site specific fertilizer recommendation in maize on the basis of farmer fields. Due to a unique characteristic of farmer field, it may be interesting to observe the pattern of soil fertility in relation to yields. Six farmer's fields and thirty soil samples were taken and analysed in the laboratory. The results showed that QUEFTS model was a valuable tool to make fertilizer recommendation by using yields as an integrated indicator. The results also showed that QUEFTS model was a promising method for establishing fertilizer recommendation for maize. The merits of model for determining Indigenous Nutrient Supply, nutrient yield limiting factors, balanced fertilizer recommendation show that QUEFTS model is a valuable tool for site specific fertilizer recommendation. Keywords: QUEFTS, recommendation, site specific, yield